The Mediterranean Diet Reduces the Risk and Mortality of the Prostate Cancer: A Narrative Review - Capurso, Cristiano; Vendemiale, Gianluigi (Frontiers in Nutrition, 2017)
Prostate cancer is the second most common cancer in the world among men, and is the fifth most common cause of cancer death among men. The aim of our review was to analyse observational and case–control studies to point out the effects of overweight and diets components on the cancer risk, particularly on risk of prostate cancer, and the effect of the Mediterranean Diet (MD) on the reduction of risk and mortality of prostate cancer. It is known that incidence and progression of cancer is multifactorial. Cancer of the large bowel, breast, endometrium, and prostate are due also to a high BMI and to high consumption of high carcinogenic dietary factors, as red and processed meat or saturated fats rich foods, and to a low consumption of vegetables and fruits. Previous meta-analysis suggested that high adherence to diet model based on the traditional MD pattern gives a significant protection from incidence and mortality of cancer of all types. The main component of the MD is olive oil, consumed in high amount by Mediterranean basin populations. In addition, phenolic compounds exert some strong chemo-preventive effects, which are due to several mechanisms, including both antioxidant effects and actions on cancer cell signalling and cell cycle progression and proliferation. The protective effect of the MD against the prostate cancer is also due to the high consumption of tomato sauce. Lycopene is the most relevant functional component in tomatoes; after activating by the cooking of tomato sauce, it exerts antioxidant properties by acting in the modulation of downregulation mechanisms of the inflammatory response. MD, therefore, represents a healthy dietary pattern in the context of a healthy lifestyle habits. In conclusion, our narrative review allows us to reaffirm how nutritional factors play an important role cancer initiation and development, and how a healthy dietary pattern represented by MD and its components, especially olive oil, could exert a protective role by the development and progression of prostate cancer